The effects of customer-brand relationship investments on customer engagement (IR) - Zuraidah Zainol (2014)
Achieving a strong customer-brand relationship is indeed a winning differentiating strategy for companies to survive in today's highly competitive marketplace. However, due to limited studies and narrow approach, the existing literature has not yet provided sufficient explanation on the contributing factors in the establishment of a strong customer-brand relationship. Recognizing the critical role of relationship investment and customer engagement, this research aims to investigate the influence of customer and brand investments on customer engagement. Specifically, this research extends the Resource Investment model by Morais et al. (2004) and empirically examines the effects of customer-brand relationship investments' dimensions on customer engagement, the effect of brand investment dimensions on customer investment dimensions, the mediating effect of customer investment dimensions and the moderating role of relationship duration. To test the proposed framework, this research adopted the positivist, deductive and quantitative approach. Data, which gathered from a quota sample of 600 mobile phone customers through the drop-off survey method, was analysed using Structural Equation Modelling (SEM). The results show that customer intrinsic investment (Cll), customer extrinsic investments (CEI) and brand social investment (BSI) significantly induce customer engagement (CE). Besides, brand social and economic investments (BSI and BEl) significantly influence crr and CEL In addition, crr and CEI partially mediate the relationship between BSI and CE, while crr fully mediate the effect of BEl on CEo Finally, the results demonstrate a minor moderating effect of relationship duration, which it only significant in the effect of crr on CEo Accordingly, the findings provide empirical evidence on the collective effect of customer-brand relationship investments as well as independent effects of the dimensions of customer-brand relationship investments on customer engagement. Further, the findings suggest that to enhance customer engagement toward brand and consequently establish a strong customer-brand relationship, companies should continually improve the customer perception of the relationship investment.